Directions of improvement of training of young wrestlers of freestyle - Ruchka Yevhen (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to prove the directions of improvement of training of young wrestlers of freestyle for the purpose of improvement of results of their competitive activity and sports skill. Material & Methods: methods are used during the research: analysis and synthesis of data of scientific and methodical literature; pedagogical observations; poll (conversation, questioning); analysis of competitive activity of young wrestlers of freestyle; testing of physical fitness; pedagogical experiment; methods of mathematico-statistical processing of results of researches. Results: it is proved that the improvement of technical-tactical training of young wrestlers of freestyle is required; the main problems in this process are defined. Conclusions: the technique of training of young wrestlers of freestyle is proved and the expediency of its use for quick adoption of optimal technical-tactical solutions by them in the conditions of competitive activity is proved. Concrete ways of tactical preparation for each action and various combinations of basic actions are offered to include in the program of CYSS for free-style wrestling.